An Epidemic of Mild Pneumonia Due to an Unusual Strain of Chlamydia psittaci - Saikku, P.; Wang, S. P.; Kleemola, M.; Brander, E.; Rusanen, E.; Grayston, J. T. (Journal of Infectious Diseases, 1985)
An epidemic of mild pneumonia was discovered during a chest radiographic survey of adolescents and young adults in two communities 110 kilometers apart in northern Finland. Antibodies to chlamydial antigens were found in 32 of 34 persons with pneumonitis. Microimmunofluorescence antibody tests suggest that the etiologic agent is closely related or identical to TW-183, an unusual strain of Chlamydia psittaci isolated from the eye of a child in Taiwan. The point prevalence of pneumonitis with antibody to TW-183 in school children at the time of the survey was high −15 and 19 patients per 1,000 students in the two communities. There was no evidence of avian transmission in the epidemic.